A Case–control Study of Major Genetic Predisposition Risk Alleles in Developing DDD in the Northeast US Population: Effects of Gene–gene Interactions. Issue 22 (15th November 2021) - Valtchinov, Vladimir I.; Zhai, Bingxue K.; Hida, Tomoyuki; Lacson, Ronilda; Raja, Ali; Hatabu, Hiroro; Khorasani, Ramin
Abstract : A case–control study of risk alleles for DDD using magnetic resonance (MR) imaging for phenotyping. After adjustment, three predictor variables had a significant association with the outcome, age (OR = 1.130, q  < 0.0001), rs143383 (OR = 1.951, q  = 0.056), and rs3737821 (OR = 2.701, q  = 0.069). A novel variant-to-variant correlation rs143383:rs763110 had a significant adjusted OR = 7.933 ( P  = 0.070). Abstract : Study Design: A case–control study of risk alleles for degenerative disc disease (DDD) using magnetic resonance (MR) imaging for phenotyping. Objective: We aim to provide the first statistically adequately powered study of the relationship between the presence of common risk alleles and occurrence of DDD in Eastern US population. Summary of Background Data: Many genetic predisposing factors have been identified in elevating the risk of DDD, including common variants in VDR, COL1A1, AGC1, COL9A2/3 genes. Methods: We utilized the Mass General Brigham (MGB) Biobank in which subjects' Medical Record is linked with genotyped data from single-nucleotide polymorphism (SNP) arrays. Subjects with lumbosacral spine MR imaging studies were used to construct the Cases cohort; the Biobank's Controls cohort was used as the Control cohort. Odds ratios (OR) and False-discovery-rate (FDR) q values from multiple-hypotheses-testing corrections were used to assess the likelihood of DDD given occurrence of the listed DDD risk alleles. Results: Four-hundred-fourteen subjects (mean age = 64, range = 27 to 94) were Cases and 925 Controls (mean age = 46, range = 21–61). A systematic search has identified 25 SNPs in 18 genes in the SNP arrays. At univariate level, rs1544410 in VDR was significantly associated with DDD for male subjects (odds ratio [OR] = 0.594, P  = 0.011). After adjustment for all significant variants and demographics, three predictor variables had a significant association with the outcome, age (OR = 1.130, q  < 0.0001), rs143383 (OR = 1.951, q  = 0.056), and rs3737821 (OR = 2.701, q  = 0.069). A novel variant-to-variant correlation rs143383:rs763110 had a significant adjusted OR = 7.933, q  = 0.070). Conclusion: In this large-scale study of common variants' correlation with the presence of DDD in the Northeast United States, we have found a novel and significant variant-to-variant interaction to be associated with the risk of developing DDD, corroborating and necessitating the inclusion of gene–gene interactions in predictive risk model development for DDD. Level of Evidence: 4